Multiplikasi dan Pigmentasi Antosianin Daun Dewa (Gynura pseudochina (L) DC) In Vitro - Nirwan, ,; Aziz, Sandra Arifin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The research consisted of two experiments, they were shoot multiplications experiment and root induction with anthocyanins content experiment. Randomized block design with two factors was used in the two experiments. In the first experiment BAP and IAA were used which were 0, 1, 2, 3 ppm and 0, 0.5 and 1 ppm, respectively. In the second experiment IAA and sucrose were used which were 0, 0.5, 1 ppm and 30, 40, 50 and 60 g/l. Addition of BAP 3.54 and 2.98 ppm without IAA to in vitro MS medium in the first experiment, significantly increased the number of shoots (33.21) and number of leaves (52.53) at 5 weeks after planting. MS medium with BAP 0.32 ppm without IAA produced maximum shoot heights (4.11 cm), while addition BAP up to 3 ppm significantly reduced number of roots and induced callus diametres (1.48 cm). Purple pink leaf colour was produced without BAP application. In the second experiment, addition of IAA 1 ppm with sucrose 52.18 g/l and IAA 1 ppm with sucose 48.36 g/l produced maximum of shoot number (15.01 shoots) and leaf number (29.16 leaves) at 8 weeks after planting, but the size of shoot and leaf were smaller. Maximum shoot height (10.03cm), number of root (35.4) and length of root (22.3 cm) were produced at the IAA 0.5 ppm and sucrose 30 g/l. The highest anthocyanins content (0.071 %) and number of plantlet (2.6) were produced by addition of sucrose 30 g/l. Anthocyanin and number of plantlet decreased quadratically with sucrose addition. Key words : Anthocyanin, In Vitro, Gynura pseudochina (L.) DC